NARATIVE RECEPTIONS OF DESIGN OF CHARACTERS IN PROSE OF ROSTISLAV ENDIK - Zalevska, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article on the material of prose Rostislav Yendyka investigated the synthesis of genres novels and stories, different types of narrator, specificity narrative style of the author, communication with the reader.